SHUHRATNING «OLTIN ZANGLAMAS» VA O‘.HOSHIMOVNING «TUSHDA KECHGAN UMRLAR» ROMANLARI ANALOGIK TALQINI - Yadgarova, M. (SCIENCE and SOCIETY, 2016)
The article deals with the analysis of novels during the repression in our country. The author of the article studies the topic of repression at the period of the former Soviet Union and at present time in the analogous aspect. The study of this topic has been done on the examples of the novels «Oltin zanglantas» by Shukhrat and «Tushda kechgan umrlar» by U.Hashimov
Keywords: topic; motive; description of spirituality; society; epoch spirituality; social environment; poetic commentary; analogous criticism; epoch